2008
DOI: 10.1037/0882-7974.23.2.315
|View full text |Cite
|
Sign up to set email alerts
|

The response-signal method reveals age-related changes in object working memory.

Abstract: Sixteen healthy young adults (ages 18-32) and 16 healthy older adults (ages 67-81) completed a delayed response task in which they saw the following visual sequence: memory stimuli (2 abstract shapes; 3,000 ms), a blank delay (5,000 ms), a probe stimulus of variable duration (one abstract shape; 125, 250, 500, 1,000, or 2,000 ms), and a mask (500 ms). Subjects decided whether the probe stimulus matched either of the memory stimuli; they were instructed to respond during the mask, placing greater emphasis on sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 85 publications
(185 reference statements)
1
14
0
Order By: Relevance
“…These findings complement those of a previously reported behavioral study. In that study of a different set of young and older participants, we also found asymptote lower in the older than the younger group, indicating lower capacity, while the x-intercept parameter did not differ across groups (Kumar et al, 2008). In that study we also found a higher rate in the young subjects, suggesting greater efficiency.…”
Section: 0 Discussionmentioning
confidence: 67%
“…These findings complement those of a previously reported behavioral study. In that study of a different set of young and older participants, we also found asymptote lower in the older than the younger group, indicating lower capacity, while the x-intercept parameter did not differ across groups (Kumar et al, 2008). In that study we also found a higher rate in the young subjects, suggesting greater efficiency.…”
Section: 0 Discussionmentioning
confidence: 67%
“…To analyze the effects of CR covariates on MPUBS and RT, we constructed two separate general linear models (GLM) that were analyzed in stages (heterogeneous slopes) (Kumar, Rakitin, Nambisan, Habeck, & Stern, 2008; Siegel, 1956). In each, we introduced various proxies for CR into our model, including score on the NART IQ and years of education (EDU).…”
Section: Methodsmentioning
confidence: 99%
“…Within such paradigms, the participants' stimulus processing is interrupted at different times after stimulus presentation (e.g., Boldini, Russo, & Avons, 2004;Boldini, Russo, Punia, & Avons, 2007;Corbett & Wickelgren, 1978;Dosher, 1981Dosher, , 1982Göthe & Oberauer, 2008;Kumar, Rakitin, Nambisan, Habeck, & Stern, 2008;Lohman, 1986;McElree & Dosher, 1989, 1993McElree, Plykkänen, Pickering, & Traxler, 2006;Miller, Sproesser, & Ulrich, 2008;Öztekin & McElree, 2006;Ratcliff, 2006;Reed, 1973;Schouten & Bekker, 1967). In this way, different intervals between stimulus presentation and the response signal can be used, allowing for an examination of the variation in the amount of processing that can occur before the response signal and, ultimately, the amount of accuracy associated with that amount of processing time.…”
Section: Studying Satsmentioning
confidence: 99%